An exploratory study on the potential of machine reading comprehension as an instructional scaffolding device in second language reading lessons. (October 2022) - Shin, Dongkwang; Lee, Jang Ho; Lee, Yongsang
Abstract: Machine reading comprehension (MRC) is a technology that analyzes text and answers questions about it. This study proposes an innovative approach to helping second language learners use this new technology as an instructional scaffolding device. We selected 100 reading comprehension test items of various types from the English section of the College Scholastic Ability Test in the Republic of Korea and analyzed them using Microsoft MRC. Then, we examined the extent to which MRC could help provide informative answers to questions. The results reveal that MRC could provide moderately-to-highly informative clues for the test items, although the MRC required additional questions to provide suitable answers for some test items. This ability to ask additional questions was found to be an essential component of effective MRC use. This study proposes how MRC could be used by second language learners in reading lessons and suggests directions for future research on MRC.